How Psychology Can Help to Solve the Problem of Fake News - Markov, Stefan (Media and Language, 2021)
The worldwide proliferation of online fake news has attracted considerable scientific attention. Apart from this specific interest in the topic, the determination of many social actors to create mechanisms in order to limit disinformation on the Internet is also quite noticeable. The major social networks are trying to impose adequate regulations within their own platforms in an appropriate and effective way, different countries and international political unions are considering and developing legislative measures against fake news, computer algorithms are being created to recognize false content. However, all these efforts will not bring the intended result if the implemented approach is fundamentally flawed. This article is an attempt to demonstrate how contemporary achievements of psychology and cognitive sciences can inform basically almost all measures against fake news. The current scientific understanding of human behavior could be very helpful in combating online disinformation, if only the planned actions and restrictions are consistent with it.
Keywords: fake news; disinformation; misinformation; psychology of fake news; nudge